Ligand screening approach to find potential inhibitors of GP1 from Ebola Virus - Rigi, Garshasb; Armand, Raham; Torktaz, Ebrahim (Archives of Advances in Biosciences, 2017)
Ebola is one of the members of filoviruses family. It causes severe hemorrhagic with the human mortality rate of 50-90%. In the initial steps of infection, it enters the host cell by Glyco protein1 (GP1). GP1 is a big subunit with the molecular weight of 130 kDa. Its N-terminal domain is responsible for attaching the host cell. In the present study, a database containing 100.000 drug like chemicals which was obtained from Zinc has been screened. The top successive hits were then analyzed regarding Lipinski rules, oral toxicity value and recorded biological properties. Finally, 3 new ligands were introduced as new theoretical inhibitors of Ebola virus entry. Hit #1 (Heptacyclo[18.7.0.02,10.03,8.011,19.012,17.021,26] heptacosa1(20),2(10),3,5,7,11(19),12,14,16,21,23,25-didecaene-9,18,27-trione) indicated the binding affinity of -10.7 kcal/mol with previous biological reports indicating no toxicity on human cell line. Hit#3 (1,1',3,3'-tetraethyl-5'-(4-nitrophenyl)spiro[1,3-diazinane-5,6'-5H-furo[2,3-d]pyrimidine]-2,2',4,4',6 pentone) with the binding affinity of -9.7 kcal/mol theoretically passed pharmacological filters and the toxicity class of 4 theoretically revealed that this hit also can be a potential anti GP1 agent. Moreover, hit#4(10-(Hydroxymethyl)-7,18-dimethoxy-6,17-dimethyl-21-methyl-11.21 diazapentacyclo[11.7.1.02,11.04,9.015,20]henicosa-4(9),6,15(20),17-tetraene-5,8,12,16,19-pentone) also indicated the binding affinity of -9.7 kcal/mol and was matched with Lipinski rules and the toxicity class 4, suggesting that it can be safe in low dose usage. Based on the pharmacological properties, hit #1, 3 and 4 are presented as the new hypothetical drugs against GP1. Moreover, hit#1 has previously been recorded as nontoxic activity on human cell line and makes it an appropriate candidate for further in vitro and in vivo studies.